International price discovery in the presence of microstructure noise - Joachim G. Grammig; Franziska J. Peter (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
This paper addresses and resolves the issue of microstructure noise when measuring the relative importance of home and U.S. market in the price discovery process of Canadian interlisted stocks. In order to avoid large bounds for information shares, previous studies applying the Cholesky decomposition within the Hasbrouck (1995) framework had to rely on high frequency data. However, due to the considerable amount of microstructure noise inherent in return data at very high frequencies, these estimators are distorted. We offer a modified approach that identifies unique information shares based on distributional assumptions and thereby enables us to control for microstructure noise. Our results indicate that the role of the U.S. market in the price discovery process of Canadian interlisted stocks has been underestimated so far. Moreover, we suggest that rather than stock specific factors, market characteristics determine information shares.
urn:nbn:de:hebis:30-62291
Keywords: F3; G15; 330; International Cross-Listings; Market Microstructure Noise; Price Discovery; Börsenkurs; Internationaler Preiszusammenhang; Noise Trading; Mikrostrukturanalyse; Kanada; USA